The Effect of Trauma Healing (Mindfulness) Therapy on Psychological Trauma Due to the Eruption of Mount Marapi West Sumatra - Fitri, Laila; Jumilia; Cleodora, Cindy (International Journal of Natural and Health Sciences, 2024)
Since 2023, Mount Marapi has erupted 116 times. There were 36 heads of families who were victims of eviction due to the eruption of Mount Marapi. The aim of this research is to determine the impact of mindfulness therapy on psychological trauma due to the eruption of Mount Marapi at the X Koto Tanah Datar Community Health Center in 2024. This type of quantitative research with a quasi-experimental design (one group pretest-posttest design). The sample for this research consisted of 12 people. This research was conducted in March - July 2024. The results of the research showed that the average level of psychological trauma in the intervention group before and after trauma healing (mindfulness) treatment was 1.008 with a standard deviation of 0.174. With statistical tests obtained a p-value of 0.000, so it can be concluded that There is an influence of providing mindfulness therapy on the level of psychological trauma due to the eruption of Mount Marapi in the work area of the Community Health Center. X Koto, Tanah Datar in 2024. It is recommended that the disaster working group at the Community Health Center create a trauma healing program because this Community Health Center is prone to disasters